2020
DOI: 10.3390/s20102946
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Adjusting Water Bolus Liquid Properties for Economic and Precise MR Thermometry Guided Radiofrequency Hyperthermia

Abstract: The potential of MR thermometry (MRT) fostered the development of MRI compatible radiofrequency (RF) hyperthermia devices. Such device integration creates major technological challenges and a crucial point for image quality is the water bolus (WB). The WB is located between the patient body and external sources to both couple electromagnetic energy and to cool the patient skin. However, the WB causes MRT errors and unnecessarily large field of view. In this work, we studied making the WB MRI transparent by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In addition to the SNR benefits, the integrated coil-array also allows for the use of advanced MR techniques, such as parallel imaging, to enable faster acquisition times (from 8.7 s in this study to 2–4 s) for correction of the impact of respiratory motion. Earlier, we showed that a further increase in SNR and acquisition speed can be achieved by using iron oxide nanoparticles in the water bolus to enable reducing the imaging field of view [ 46 ]. All benefits combined can further help the adoption of MR-guided hyperthermia treatments and pave the way for wider acceptance in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the SNR benefits, the integrated coil-array also allows for the use of advanced MR techniques, such as parallel imaging, to enable faster acquisition times (from 8.7 s in this study to 2–4 s) for correction of the impact of respiratory motion. Earlier, we showed that a further increase in SNR and acquisition speed can be achieved by using iron oxide nanoparticles in the water bolus to enable reducing the imaging field of view [ 46 ]. All benefits combined can further help the adoption of MR-guided hyperthermia treatments and pave the way for wider acceptance in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging and -thermometry on the other hand could benefit from presence of the water bolus by homogenizing the magnetic field, called “shimming”. Sumser et al observed that for hyperthermia purposes, the water bolus fluid should be spiked with Fe 3 O 4 nanoparticles in order to improve the signal-to-noise ratio [ 57 ]. This is in contrast to standard water baths, which frequently use demineralized water.…”
Section: Hyperthermia Devicesmentioning
confidence: 99%
“…[2][3][4][5][6][7] Moreover, MRI is the most often used noninvasive way to estimate the temperature, whilst undergoing hyperthermia therapy. [8][9][10][11][12] With the use of high-field MRI, researchers have analysed the characteristics and diagnosis methods of cancerous organs using a human phantom model. 12,13 In case studies involving small animal experiments, where a heating and temperature monitoring system is used, it is vital to precisely measure the energy translation properties (excitation power, duration of temperature and simulation period) to establish a robust hyperthermia protocol in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…This method is capable of diagnosing and differentiating between healthy and cancerous tissues 2–7 . Moreover, MRI is the most often used non‐invasive way to estimate the temperature, whilst undergoing hyperthermia therapy 8–12 . With the use of high‐field MRI, researchers have analysed the characteristics and diagnosis methods of cancerous organs using a human phantom model 12,13 .…”
Section: Introductionmentioning
confidence: 99%